Children of the Fleet - Card, Orson Scott (New York, NY : Tom Doherty Associates, 2017)
The story of the Fleet in space, parallel to the story on Earth, told during the time that Peter Wiggin and Bean are consolidating the Hegemony on Earth. The terraformed Formic worlds are open to settlement by humans, and the International Fleet becomes the arm of the Ministry of Colonization, run by Hirum Graff. MinCol now runs Fleet School on the old Battle School station, and still recruits very smart kids to train as leaders of colony ships and colonies. Dabeet Ochoa is a very smart kid. Top of his class in every school, but he doesn't think he has a chance at Fleet School. He has no connections to the Fleet, that he knows of, until the day that Colonel Graff arrives at his school for an interview.
Keywords: War games -- Fiction; Military education -- Fiction; Schools -- Fiction; Child soldiers -- Fiction; Space warfare -- Fiction; Science fiction